Addressing fuel recycling in solid oxide fuel cell systems fed by alternative fuels. (15th October 2017) - Rokni, M.
Abstract: An innovative study on anode recirculation in solid oxide fuel cell systems with alternative fuels is carried out and investigated. Alternative fuels under study are ammonia, pure hydrogen, methanol, ethanol, DME and biogas from biomass gasification. It is shown that the amount of anode off-fuel recirculation depends strongly on type of the fuel used in the system. Anode recycling combined with fuel cell utilization factors have an important impact on plant efficiency, which will be analysed here. The current study may provide an in-depth understanding of reasons for using anode off-fuel recycling and its effect on plant efficiency. For example, it is founded that anode recirculation is not needed when the plant is fed by ammonia. Further, it is founded that when the system is fed by pure hydrogen then anode recirculation should be about 20% of the off-fuel if fuel cell utilization factor is 80%. Furthermore, it is founded that for the case with methanol, ethanol and DME then at high utilization factors, low anode recirculation is recommended while at low utilization factors, high anode recirculation is recommended. If the plant is fed by biogas from biomass gasification then for each utilization factor, there exist an optimum anode recirculation at which plant efficiency maximizes. Highlights: When and where anode recirculation in a SOFC based plant is needed. Alternative fuels are used in the study such as ammonia, methanol, ethanol, DME and biogas in this study. Concrete suggestions are given to use or not use the fuel recirculation. Design of SOFC based plant with anode recirculation and with alternative fuels.